Retinoic acid increases the effect of bone morphogenetic protein type 2 on osteogenic differentiation of human adipose-derived stem cells - Ariadne Cristiane Cabral CRUZ; Francielle Tramontini Gomes de Souza CARDOZO; Ricardo de Souza MAGINI; Cláudia Maria Oliveira SIMÕES (University of São Paulo, 2019)
Abstract Bone morphogenetic protein type 2 (BMP-2) and retinoic acid (RA) are osteoinductive factors that stimulate endogenous mechanisms of bone repair which can be applied on management of osseous defects in oral and maxillofacial fields. Objective Considering the different results of RA on osteogenesis and its possible use to substitute/potency BMP-2 effects, this study evaluated the outcomes of BMP-2, RA, and BMP-2+RA treatments on in vitro osteogenic differentiation of human adipose-derived stem cells (ASCs) and the signaling pathway(s) involved. Material and Methods ASCs were treated every other day with basic osteogenic medium (OM) alone or supplemented with BMP-2, RA, or BMP-2+RA. Alkaline phosphatase (ALP) activity was determined using the r-nitrophenol method. Extracellular matrix mineralization was evaluated using von Kossa staining and calcium quantification. Expression of osteonectin and osteocalcin mRNA were determined using qPCR. Smad1, Smad4, phosphorylated Smad1/5/8, BMP-4, and BMP-7 proteins expressions were analyzed using western blotting. Signaling pathway was evaluated using the IPA® software. Results RA promoted the highest ALP activity at days 7, 14, 21, and 28, in comparison to BMP-2 and BMP-2+RA. BMP-2+RA best stimulated phosphorylated Smad1/5/8 protein expression at day 7 and Smad4 expression at days 7, 14, 21, and 28. Osteocalcin and osteonectin mRNA expressions were best stimulated by BMP-2+RA at day 7. Matrix mineralization was most improved by BMP-2+RA at days 12 and 32. Additionally, BMP-2+RA promoted the highest BMP signaling pathway activation at days 7 and 14, and demonstrated more activation of differentiation of bone-forming cells than OM alone. Conclusions In summary, RA increased the effect of BMP-2 on osteogenic differentiation of human ASCs.